TRADISI PUNGGUAN DI KAMPUNG JAWA TONDANO KABUPATEN MINAHASA - Lamantu, Rabbia Safitri; Otta, Yusno Abdullah; Rusdiyanto, Rusdiyanyo (Jurnal JINNSA (Jurnal Interdipliner Sosiologi Agama), 2021)
This research is entitled “History of the Pungguan Tradition in Kampung Jawa Tondano, Minahasa Regency”, the main problems of this research are: (1) How is the origin of the Pungguan tradition in Kampung Jawa Tondano? (2) What are the Islamic values contained in the Pungguan tradition in the Kampung Jawa Tondano? (3) Why does the Pungguan tradition still survive today? The approach in this research was the Historical and Phenomenological Approach. The Pungguan tradition specifically aims to pray for the spirits of the deceased ancestors to ascend to the top, that is rise before Allah SWT. The Pungguan tradition in Kampung Jawa Tondano is carried out by visiting the graves of deceased ancestors and relatives. The data in this study were qualitative data sourced from primary and secondary data. Primary data sources were data sources that come from imam,vice imam, elders, the Chairperson of the Jaton LPM Cultural Arts Coordinator, the commonity and the local goverment. While the secondary data sources were books, journals, and theses related to the themes discussed. Data collection techniques were observation, interviews, and documentation. In analyzing the data, qualitative descriptive analysis was carried out, namely explaining or proposing an assessment of all problems, then deductive and inductive conclusions were drawn. Deductive is drawing conclusions about specific truths from accepted general truths. While inductive is a way of inferring general truths from specific truths, so that is research can be understood. The result of this research is the history of the Pungguan tradition in Kampung Jawa Tondano was brought directly by Kiai Modjo and his followers around the middle of the XVIII cantury. The Islamic values obtained from this tradition are the values of faith, worship, Ukhuwah Islamiyah, and cleanliness. The reason the Pungguan tradition still survives today because it respects, maintains, and preserves the traditions left by the ancestors. Keyword: Pungguan Tradition, Kampung Jawa Tondano Abstrak Penelitian ini berjudul “Sejarah Tradisi Pungguan di Kampung Jawa Tondano Kabupaten Minahasa”, pokok permasalahan dari penelitian ini adalah: (1) Bagaimana asal mula tradisi Pungguan di Kampung Jawa Tondano? (2) apa saja nilai-nilai Islam yang terkandung dalam tradisi Pungguan di Kampung Jawa Tondano? (3) mengapa tradisi Pungguan masih bertahan hingga kini? Pendekatan yang digunakan dalam penelitian ini adalah Pendekatan Sejarah dan pendekatan Fenomenologi. Tradisi Pungguan secara khusus bertujuan untuk mendoakan arwah para leluhur yang sudah meninggal naik ke atas, yakni naik ke hadapan Allah Swt. Tradisi Pungguan di Kampung Jawa Tondano dilakukan dengan ber ziarah ke makam para leluhur dan kerabat yang sudah meninggal dunia. Data dalam penelitian ini adalah data kualitatif yang bersumber dari data primer dan sekunder. Sumber data primer adalah sumber data yang berasal dari imam masjid, wakil imam masjid, sesepuh, Ketua Kord. Seni Budaya LPM Jaton, masyarakat serta pemerintah setempat. Sedangkan sumber data sekunder adalah buku, jurnal, dan skripsi yang berhubungan dengan tema yang dibahas. Teknik pengumpulan data yaitu dengan observasi, wawancara, dan dokumentasi. Dalam menganalisis data dilakukan analisis deskriptif kualitatif yaitu menjelaskan atau mengemukakan pengkajian terhadap seluruh permasalahan, kemudian ditarik kesimpulan secara deduktif dan induktif. Deduktif yaitu pengambilan kesimpulan mengenai kebenaran khusus dari kebenaran umum yang diterima. Sedangkan induktif yaitu cara menyimpulkan kebenaran umum dari kebenaran-kebenaran yang khusus, sehingga penelitian ini bisa dimengerti dan dipahami. Hasil dari penelitian ini yaitu sejarah tradisi Pungguan di Kampung Jawa Tondano di bawa langsung oleh Kiai Modjo beserta pengikutnya sekitar pertengahan abad XVIII. Nilai-nilai Islam yang didapat dari tradisi ini adalah nilai akidah, nilai ibadah, nilai ukuwah islamiyah, dan nilai kebersihan. Dan alasan tradisi Pungguan masih bertahan hingga kini adalah karena menghormati, menjaga, dan melestarikan tradisi yang sudah ditinggalkan oleh paraleluhur. Kata Kunci: Sejarah, Tradisi Pungguan, Kampung Jawa Tondano